Dust in Svalbard: local sources versus long-range transported dust (SVALDUST) - Di Mauro, Biagio; Cappeletti, David; Moroni, Beatrice; Mazzola, Mauro; Gilardoni, Stefania; Luks, Bartłomiej; Nawrot, Adam; Lewandowski, Marek; Dagsson Waldhauserova, Pavla; Meinander, Outi; Wittmann, Monika; Kaspari, Susan; et al. (Svalbard Integrated Arctic Earth Observing System, 2023)
This is chapter 3 of the State of Environmental Science in Svalbard (SESS) report 2022. Dust consists of fine and coarse particles that travel in the atmosphere and are deposited on the Earth’s surface. Dust particles deposited on snow and ice can cause snow darkening and contribute to melting. In this chapter, we summarise existing knowledge on local and long-range dust sources in Svalbard, and describe current methodologies for studying dust from both an observational and modelling perspective. Dust science in Svalbard is still in its infancy; future research will help to disentangle the complex role of dust in the Svalbard environment.